2019
DOI: 10.1177/0300060519862076
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA NORAD induces cell proliferation and migration in prostate cancer

Abstract: Objectives Prostate cancer (PCA) is the deadliest urological disease affecting men worldwide. Long noncoding RNA activated by DNA damage (NORAD) levels are increased in many cancer types, and induce cancer cell progression. However, little is known about the biological functions of NORAD in PCA. Methods In this work, the roles of NORAD in cell proliferation, migration, and apoptosis were examined by Cell Counting Kit-8, scratch wound, and annexin V-fluorescein isothiocyanate/propidium iodide staining assays, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Another research revealed that NORAD was upregulated in colorectal cancer tissues, and NORAD inhibition induced apoptosis and constrained invasion, migration, and proliferation of colorectal cancer cells [ 31 ]. Zhang et al stated that NORAD exhaustion constrained migration, proliferation, and accelerated apoptosis of PCa cells [ 13 ]. We also observed that NORAD expression was boosted in PCa tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research revealed that NORAD was upregulated in colorectal cancer tissues, and NORAD inhibition induced apoptosis and constrained invasion, migration, and proliferation of colorectal cancer cells [ 31 ]. Zhang et al stated that NORAD exhaustion constrained migration, proliferation, and accelerated apoptosis of PCa cells [ 13 ]. We also observed that NORAD expression was boosted in PCa tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, NORAD depletion repressed epithelial ovarian cancer advancement [12]. Furthermore, NORAD was concerned with the tumorigenesis of PCa [13]. Nevertheless, the regulatory mechanism of NORAD in PCa progression has been not been well explained.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the last several decades have indicated that NORAD serves a pivotal regulator in the occurrence and progression of a variety of malignancies, including gastric cancer, prostate cancer, and osteosarcoma [ 10 , 15 , 16 ]. Overexpression of NORAD is closely related to poor prognosis in various patients with cancer, such as esophageal squamous cell carcinoma, gastric cancer, and ovarian cancer [ 17 – 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some lncRNAs contribute to DDP resistance in NSCLC (Hu et al 2017;Tian et al 2019). Recently, noncoding RNA activated by DNA damage (NORAD) has attracted attention because of its promoting role in tumour progression (Liu et al 2016;Li et al 2018a;Zhang et al 2019). Zhang et al have shown that NORAD promotes colorectal tumour growth by inhibiting miR-202-5p (Zzhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%